Variation for Qualitative Fruit Parameters among Seed Production Areas of Teak (Tectona grandis L.F) in Kerala - Nagesh Prabhu, H.; Gunaga, Rajesh P.; Surendran, T. (Indian Forester, 2007)
Teak is an important plantation species of the tropics. Due to its unique wood properties, it is also widely planted out side its natural range. Variation present in reproductive traits is most important in tree improvement programmes. Seed production areas and seed sources were identified for qualitative variations in fruit traits such as nature of fruit calyx attachment, hairiness and splitting nature. Considering seed production areas, variations were found to be strong between SPAs and within seed sources differences were negligible. Splitting nature of fruits was also observed as strong seed sources effect, while SPAs located in southern seed sources of Kerala, were without splitting nature. These variations could be helpful during identification of seeds of different seed sources and it may have important role on germination.